A Whānau Ora Journey of Māori Men with Chronic Illness: A Te Korowai analysis. Issue 2 (June 2013) - Kidd, Jacquie; Gibbons, Veronique; Kara, Erena; Blundell, Rawiri; Berryman, Kay
The Oranga Tāne Māori research project explored the views of tāne Māori (Māori men) with a chronic disease or cancer, and their whānau (families), to discover how they experienced their health care in relation to whānau ora (healthy families). The first phase of developing this research involved developing a local whānau ora framework called Te Korowai. Interviews were undertaken with 47 tāne Māori with chronic disease or cancer and 15 support people. The men had received or were currently receiving care for one or more chronic diseases. Data were analysed using Te Korowai as a conceptual framework. Findings included the foundational importance of "being Māori" as an enabler for health decision-making and service engagement, and whakamā (shyness, embarrassment) as a barrier to effective service provision. Health professionals are urged to look to how they can re-engage individuals and whānau, and to prioritize relationship building and respectful engagement.